Wear and corrosion of composite coated AISI 4340 steel exposed to jatropha curcas biodiesel - Maleque, Md. Abdul; ghazal , Belal Ahmed; Ali, Mohd Yeakub; Hayyan, Maan; Hashim, Mohd Ali; Ahmed, Abu Saleh (2014)
This study presents the effect of jatropha curcas biodiesel on the wear and corrosion behavior of composite coated AISI 4340 low alloy steel surface which was modified by TIG torch surface melting technique. Ferro-titanium carbide (Fe-TiC) composite coating layer of 970 µm thickness was produced by preplacement of 1 mg/mm2 TiC particulate into the surface of AISI 4340 steel and glazed at 1344 J/mm heat input using an electric arc generated from the tungsten electrode that melt the powder with substrate material to form a composite layer. The micrograph of the composite coated surface modified steel showed formation of TiC dendrites that densely populated at the of the melt pool which contributes to the high hardness value. The wear behavior of the composite coated steel was investigated using a universal ball-on-disc tribometer under biodiesel lubricated wear condition. The corrosion behavior of the composite coated steel was studied using tafel extrapolation method in biodiesel environment. The composite coating enhances the wear behavior by reducing the wear volume loss approximately by factor of two. The wear worn surface micrograph shows abrasive type of wear and pitting corrosion holes as a dominant wear mechanisms for AISI 4340 steel, on the other hand smooth wear scars for composite coated steel. The tafel curve showed reduction of corrosion current density of the surface modified steel compared to the alloy street substrate.